Attitudes towards Research in Higher Education Students - Camacho Torres, Julissa (2022)
In recent years, there have been positive changes in teaching and research; however, these are insufficient. The responsibility falls on the university, the undeniable center of knowledge, since it must embrace teaching and research, and transform it so that it results in the greatest economic, political and social development of the country. The objective was to know the attitude towards research in Education students of a national university in Metropolitan Lima 2022. The sample consisted of 110 students from the Faculty of Education during the year 2022. The information was collected through the version revised scale of attitudes towards research (EACIN). The results indicated that70% had a bad attitude towards research; 21.8%, regular level and 8.2%, good attitude. Interest in research was similar between the fair and poor levels, 45.5% and 42.7%, respectively; only 11.8% presented a good level. 68.2% showed a poor vocation for research; 25.5%, regular level and 6.4%, good. The evaluation of the investigation had the highest percentage in the bad level, 81.8%; regular level with 14.5% and good valuation 3.6%